Reservation Information System Using Best-Fit Algorithm at Coworking Space Nutrihub Makassar - Murni, Murni; Akib, Faisal; Yusuf, Farida (Newinera Publisher, 2025)
Coworking space, is a phenomenon that introduces a modern way of working with flexibility and collaboration. With the establishment of Nutrihub Makassar Coworking space by Nutrifood, there is an opportunity to build extensive partnerships in an organized work atmosphere. The problem faced by Nutrihub Makassar Coworking Space is the reservation system that still uses WhatsApp, which has limitations in presenting information. The reservation process requires the exchange of details such as date, time, number of guests, and special requirements. In chat format, this information is difficult to organize properly, less efficient can result in suboptimal scheduling, with the risk of disrupting the event or service. A careful approach is needed in managing reservations to overcome these challenges. This study uses a system design method that includes needs analysis, system design, and implementation. And illustrates that the implementation of a reservation system using the best fit algorithm in coworking space can have a positive impact, such as optimizing space utilization, increasing operational efficiency, and customer satisfaction. During the testing process, this system has been thoroughly tested using black box and System Usability Scale (SUS) testing. The results of the black box test show that this system runs well and is in accordance with user expectations. The results of the System Usability Scale (SUS) test showed a final result of 83.75 and obtained an Acceptability Range of “Acceptable”. This shows that the usability or usefulness of the reservation information system at the Nutrihub Makassar coworking space is feasible to use and can be applied well to users.